Implementation of Judicial Pardon in the Reformation of the Criminal Justice System Based on Legal Certainty - Jelindo, Reyga; Winjaya Laksana, Andri (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The concept of judicial pardon is regulated in Article 54 paragraph (2) of Law Number 1 of 2023 concerning the Criminal Code. This article regulates the qualifications for imposing a judicial pardon as a basis for the judge to decide whether or not to impose a criminal penalty if the defendant's actions are included in the scope of the crime. The objectives of the research in this study: 1) to find out and analyze the implementation of judicial pardon in the current criminal justice system; 2) to find out and analyze the weaknesses in the implementation of judicial pardon in the renewal of the criminal justice system; 3) to find out and analyze the implementation of judicial pardon in the renewal of the criminal justice system based on legal certainty. The approach method in this study is by using the legislative approach, conceptual approach and case approach/comparative approach. The data used are primary and secondary data which will be analyzed qualitatively. The research problems are analyzed using the theory of legal certainty and the theory of the legal system. The results of the study concluded that: 1) The implementation of judicial pardon in the current criminal justice system reform, namely the problems surrounding the development of the current criminal justice system, shows that this system is considered no longer able to provide protection for human rights and transparency for the public interest. The individualistic and formal procedural criminal system has ignored the reality of the value of peace so that it is not used as a basis for the elimination of criminal punishment; 2) The weaknesses of the implementation of judicial pardon in the renewal of the criminal justice system based on legal certainty consist of weaknesses in the legal substance aspect, weaknesses in the legal structure aspect. The weakness of the substance aspect is that there are no regulations that clearly categorize crimes in the RKUHP into minor or serious crimes. The weakness of the legal structure aspect is that when judges experience a dilemma when making a decision, they can use Judicial Pardon, or the judge's forgiveness. The weakness of the legal culture aspect is that if the sense of justice based on this law is considered by the judge to have been fulfilled through the decision he made, then it is not necessarily felt to be fair by the community, or some even state that the decision is truly unfair, and vice versa; 3) The implementation of judicial pardon in the renewal of the criminal justice system based on legal certainty that the application or imposition of a judge's pardon decision must go through several considerations, such as the lightness of the act, the personal condition of the perpetrator, or the circumstances surrounding the act at that time or afterward, as well as considering aspects of justice and humanity. The application of the judge's pardon decision must later be balanced with the integrity of law enforcers.